2021
DOI: 10.1155/2021/9863155
|View full text |Cite
|
Sign up to set email alerts
|

Impact of YouTube Advertising on Sales with Regression Analysis and Statistical Modeling: Usefulness of Online Media in Business

Abstract: Computer technology plays a prominent role in almost every aspect of daily life including education, health care, online shopping, advertising, and even in homes. Computers help to make daily tasks much easier and convenient. Among social media, YouTube is a well-known social sharing networking service. As more and more people join social media and become everyday users, brands have also increased their online engagement. However, it is still unclear how to effectively measure value and return on advertising u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…The study concluded therefore that companies may miss an opportunity if existing YouTube channels are not used proactively to manage social connections (Bonsón et al, 2014). An increased engagement of stakeholders, including customers, is also identified in the work of Zhou et al (2021). They found that YouTube is an effective medium for advertising.…”
Section: The Youtube Video Platformmentioning
confidence: 99%
“…The study concluded therefore that companies may miss an opportunity if existing YouTube channels are not used proactively to manage social connections (Bonsón et al, 2014). An increased engagement of stakeholders, including customers, is also identified in the work of Zhou et al (2021). They found that YouTube is an effective medium for advertising.…”
Section: The Youtube Video Platformmentioning
confidence: 99%
“…Dentro de este contexto, se identificó que la publicidad online de YouTube está asociada con las ventas de una empresa, denotando que cuanto más dinero se gaste en la publicidad de YouTube mayores serán las ventas y los beneficios, permitiendo a una marca superar a sus competidores y establecer claras ventajas competitivas dentro del entorno digital. En marzo de 2019, esta plataforma llegó a los 1,5 mil millones de usuarios activos mensuales y atrajo la atención de diferentes firmas comerciales que han empezado invertir cada vez más en publicidad [10].…”
Section: A Publicidad Para El Mundo Digital Y Tendencias En El Compor...unclassified